Gastrointestinal and Mesenteric Amyloidosis: Review of CT and MRI Findings - Alkukhun , A..; Czeyda-Pommersheim , F.; Menias , C.; Sugi , M.; Revzin , M. (Seram, 2021)
Background Information: Amyloidosis is a rare medical condition characterized by extracellular deposition of abnormal fibrillar precursor proteins called amyloid, that accumulate in an insoluble form in organs or tissues. Occasionally, it can present as localized tumor-like deposits without systemic involvement and can be found in multiple systems in the abdomen and pelvis. The gastrointestinal system is the most common organ that is involved in the primary and secondary amyloidosis. In this exhibit, we will discuss common CT and MRI findings of amyloidosis in the gastrointestinal system and the mesentery. Educational Goals/Teaching Points: Review spectrum of CT and MRI findings of amyloidosis in the gastrointestinal system and the mesentery and highlight differentiating findings from other pathologies. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: In this educational exhibit, we will review CT and MRI characteristics of gastrointestinal amyloidosis including intestinal wall thickening, intestinal dilatation, splenomegaly, organ infiltration, and omental and mesenteric deposits. Conclusion: There are multiple ways that amyloidosis can present as and recognizing its radiological features of the most common organ involved is a vital key in the management of a highly morbid disease.